The Contextualization of Hadith Regarding the Prohibition of Damaging Corpses in the Law of Autopsy - Hardivizon, Hardivizon; Firdaus, Firdaus; Syarif, Makmur (Mashdar: Jurnal Studi Al-Qur'an dan Hadis, 2023)
This study aims to review the hadiths regarding the prohibition of damaging corpses and contextualize them with the law of autopsy. The approach used is the hermeneutics offered by Hassan Hanafi in understanding the text of revelation as a legal source. This approach involves building three types of awareness: 1) historical awareness (asy-syu'ur at-tarikhy), 2) eidetic awareness (asy-syu'ur at-ta'ammuli), and 3) praxis awareness (asy-syu'ur al-'amali). The findings of this study are as follows: 1) there are two hadiths that contain the prohibition of damaging corpses, the first narrated by Muslim, and the second by Abu Daud; 2) both hadiths that prohibit damaging corpses are of high quality (sahih); 3) the prohibition of damaging corpses applies in normal situations, but in emergencies, the use of body parts of the deceased according to necessity is allowed; 4) autopsy, whether for autopsy purposes or as a learning tool for medical students, is categorized as an emergency need and is therefore permissible according to Islamic law